2017
DOI: 10.1016/j.jretconser.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Integration of standardization and customization: Impact on service quality, customer satisfaction, and loyalty

Abstract: The basic objective of this study is to analyse the direct and indirect impacts of standardization and customization on customer satisfaction and loyalty through service quality. The service quality has two dimensions: technical quality and functional quality. A framework is developed by extending Grӧnroos' model of service quality by including the antecedents of service quality. A questionnaire-based survey collected data from 315 customers of three service industries: healthcare, hospitality, and education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
229
1
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(275 citation statements)
references
References 38 publications
20
229
1
25
Order By: Relevance
“…It means customer satisfaction has a positive direct effect on customer loyalty. These results are consistent with studies by Kasiri et al (2017);Picón (2014), Ladhari and Leclerc (2013); Kuo et al (2009);Sheng and Liu (2010); Akbar and Parvez (2009) and Chu et al (2012). They found that customer satisfaction had a positive and significant influence on customer loyalty.…”
Section: • the Impact Of Customer Satisfaction On Customer Loyaltysupporting
confidence: 92%
“…It means customer satisfaction has a positive direct effect on customer loyalty. These results are consistent with studies by Kasiri et al (2017);Picón (2014), Ladhari and Leclerc (2013); Kuo et al (2009);Sheng and Liu (2010); Akbar and Parvez (2009) and Chu et al (2012). They found that customer satisfaction had a positive and significant influence on customer loyalty.…”
Section: • the Impact Of Customer Satisfaction On Customer Loyaltysupporting
confidence: 92%
“…Various studies have found that a higher level of customer satisfaction ultimately leads to greater customer loyalty and word of mouth recommendations (YOO et al 2015;GUO et al 2009;LAI et al 2009;KASIRI et al 2017) The end user in construction can be the buyer of products and services. Customers in construction differ from those in other industries and their main disadvantage is the lack of experience.…”
Section: The Concept Of Customer Satisfactionmentioning
confidence: 99%
“…Upoznatost ispitanika sa predloženim standardima Barjaktarović, 2013;HerasSaizarbitoria et al, 2015;Kasiria et al, 2017). Drugi prepoznatljiv standard od strane ispitanika bio je ISO.…”
Section: Tabelaunclassified
“…Gosti bi pre svega znali šta mogu da očekuju u objektima koji ih primenjuju, ali i načine kako da se prevaziđu eventualni problem sa kojima se susreću u toku svog boravka u hotelima. Postoje primeri dobre prakse (Heras-Saizarbitoria et al, 2015;Kasiria et al, 2017) kako primena standarda u hotelijerstvu pomaže u prevazilaženju jaza između očekivanog i percepiranog kvaliteta usluga. …”
Section: Tabelaunclassified